2013
DOI: 10.1073/pnas.1303178110
|View full text |Cite
|
Sign up to set email alerts
|

Water diffusion in brain cortex closely tracks underlying neuronal activity

Abstract: Neuronal activity results in a local increase in blood flow. This concept serves as the basis for functional MRI. Still, this approach remains indirect and may fail in situations interfering with the neurovascular coupling mechanisms (drugs, anesthesia). Here we establish that water molecular diffusion is directly modulated by underlying neuronal activity using a rat forepaw stimulation model under different conditions of neuronal stimulation and neurovascular coupling. Under nitroprusside infusion, a neurovas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
82
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 72 publications
(106 citation statements)
references
References 40 publications
(67 reference statements)
15
82
1
Order By: Relevance
“…Recently, much attention has been paid to this technique because it is a sensitive probe that can be used under physiological conditions to evaluate acute responses associated with neuronal firing (13,16,19) and delayed changes that are correlated with molecular processes for the formation of LTP or LTD (20). Our results support a potential use of DWI techniques to estimate plasticity-related changes in nonstimulated remote regions after repetitive brain stimulation.…”
Section: Discussionsupporting
confidence: 72%
See 1 more Smart Citation
“…Recently, much attention has been paid to this technique because it is a sensitive probe that can be used under physiological conditions to evaluate acute responses associated with neuronal firing (13,16,19) and delayed changes that are correlated with molecular processes for the formation of LTP or LTD (20). Our results support a potential use of DWI techniques to estimate plasticity-related changes in nonstimulated remote regions after repetitive brain stimulation.…”
Section: Discussionsupporting
confidence: 72%
“…Water diffusion is altered by the structures of gray matter (12). DWI can be used to evaluate morphological changes in cortical microstructures (13)(14)(15)(16)(17)(18)(19) and can function as a probe to estimate immediate and transient changes in water diffusion that are associated with ischemia (17) or neuronal firing (13,16,19) and delayed and persistent changes that are associated with long-term plasticity in experimental settings (20) or pathological conditions (15,18,21). Here, using DWI techniques, we examined whether subthreshold, low-frequency (<1 Hz) rTMS to the left primary motor cortex (M1), a protocol that induces LTD-like plasticity (22, 23), increased water diffusion in the left M1 and other regions after the end of rTMS.…”
mentioning
confidence: 99%
“…In particular, diffusion MRI, a method to measure the apparent diffusivity of water within tissues (7)(8)(9), has been suggested as a direct functional imaging method to detect neuronal activity (10)(11)(12)(13). Early in vivo experiments in both humans and animals reported small but significant increases in highly diffusion-weighted MRI signals, which were ascribed to changes directly induced by the underlying neuronal activity rather than indirect hemodynamic changes (10)(11)(12)(13).…”
mentioning
confidence: 99%
“…Consistent with this argument are the previous findings by Tsurugizawa et al. (2013). In this animal study, DfMRI signal changes concordant with the induced neural activity were found under conditions of administered nitroprusside, which is known to induce neurovascular decoupling.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence demonstrating the continued presence of diffusion signal changes following the inhibition of neurovascular coupling has provided support for this distinct signal source (Tsurugizawa et al. 2013). This is in agreement with studies identifying restrictions in water diffusion induced by neuronal activity in ex vivo samples devoid of vasculature (Kohno et al.…”
Section: Introductionmentioning
confidence: 99%